Pathogenicity and Molecular Characterisation of the VP2 Gene of Infectious Bursal Disease Virus - Mahfuzul Hoque, Md (2001)
Pathogenicity of four infectious bursal disease virus (IBDV) isolates was studied on specific-pathogen-free (SPF) chickens. Chickens inoculated with isolates 92/04, 94/B551 and 97/61 developed severe clinical manifestations with a high mortality ranging from 70-80%, whereas the 94/273 isolate caused 10% mortality. However, regardless of the isolates, significant differences (p< 0.05) were noted in the bursal scoring lesions and bursa to body weight ratio index in the infected groups in comparison to the control groups. The isolate 94/273 had limited and comparatively less haemorrhagic lesions in the bursal tissues. However, the presence of severe haemorrhagic lesions in the bursal tissues along with the non-bursal tissues (muscles, thymus, spleen and at the junction of proventriculus and gizzard) were found only in the 92/04, 97/61 and 94/B551 isolates. The VP2 gene (1351 bp) of the isolates (92/04, 94/273 and 94/8551) was amplified and cloned and the sequences were compared with other 18DV strains. All the isolates have the unique amino acid residues at positions P222A, V2561, and L2941 as found in other vvlBDV strains. Restriction fragment length polymorphism (RFLP) and sequence analysis of the VP2 hypervariable region also indicated that all the isolates can be classified as vvlBDV based on the presence of Sspl and Taql sites at the nucleotide positions 1011 and 833, respectively. All the isolates except 94/273 also have a Styl site at nucleotide position 888. The absence of Styl site in this isolate is associated with amino acid substitution at 254 from G to S in variant strain. The 94/273 also has an amino acid substitution at 270 from A to E as found in apathogenic IBDV. Thus, this is a first report on the isolation of vvlBDV with some genotypic characteristic of variant and apathogenic IBDV strains. The 94/B551 also has one amino acid substitution at position 300 E to S, which is uncommon among other vvlBDV isolates. Based on the RFLP analysis the Malaysian (92/04, 941273 and 97/61) and Bangladeshi (94/B551) isolates can be differentiated using the restriction enzymes Pstl, Mbol and Taql. The deduced VP2 amino acids encoded by 92/04 is identical to the vvlBDV strains from Israel, Japan and UK, whereas the other isolates (94/273 and 94/B551) have one to three amino acid substitutions, indicating that the vvlBDV is evolving. However, the phylogenetic analysis suggested that the isolates are very close to each other and all of them may have derived from same origin as the vvlBDV strains isolated from China, Japan and Europe.